2009
DOI: 10.1093/rheumatology/kep021
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of obstructive sleep apnoea syndrome in ankylosing spondylitis patients

Abstract: The prevalence of OSAS in AS patients is higher than reported in the general population. The diagnosis of OSAS should be kept in mind and OSAS symptoms should be considered especially in AS patients at the age of >or=35 years and in AS patients with a disease duration of >or=5 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
3
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 16 publications
3
36
3
3
Order By: Relevance
“…9 The other study found an OSAS prevalence of 22.6% based on PSG examination in AS patients. 10 Considering that the OSAS prevalence is 2-7% in the normal population, 21 OSAS prevalence is substantially high in our study as well as in both of the other studies.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…9 The other study found an OSAS prevalence of 22.6% based on PSG examination in AS patients. 10 Considering that the OSAS prevalence is 2-7% in the normal population, 21 OSAS prevalence is substantially high in our study as well as in both of the other studies.…”
Section: Discussionsupporting
confidence: 60%
“…These findings suggest that OSAS prevalence increased in patients with advanced cervical vertebral disease (increased occiput-to-wall distance and neck thickness) causing oropharyngeal airway obstruction and tracheal compression. In fact, Solak et al 10 also found a greater occiput-to-wall distance and neck thickness in patients with OSAS even though their results could not reach statistical significance, most probably due to the limited sample size. This was overcome by a larger sample size in our study.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The method of collection of sleep data varied within the 15 studies as shown in Table 2 . Two studies included objective measurements of sleep: polysomnography (PSG), [ 21,35 ] and measurement of Apnoea-Hypopnoea Index (AHI) [ 35 ]. Both studies supplemented objective data with subjective data.…”
Section: Resultsmentioning
confidence: 99%
“…Two small uncontrolled studies reported OSA prevalences of 12% and 23% in ankylosing spondylitis (AS) patients, compared to 1% to 9% in the general population. 5,6 Psoriatic arthritis (PsA) has been associated with sleep interference independent of body mass index (BMI), 7 and a higher prevalence of OSA has been reported in psoriasis patients compared to controls. 8 Various mechanisms have been proposed to explain the high prevalence of OSA in SpA patients including (1) glucocorticoidinduced weight gain, (2) compression of the oropharyngeal airway by the cervical spine, and (3) systemic infl ammation.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%